TOWARDS SHARI’AH COMPLIANT FOOD TRUCK TRANSACTIONS CONCEPT AND THE RELEVANCE OF THEIR APPLICATION: AN OVERVIEW - Nurul Hidayah Awang @ Ab Rahman; Nurul Izzah Noor Zainan; Mohd Khairul Anuar Ismail; Nik Muniyati Nik Din; Zanirah Mustafa @ Busu (International Journal of Accounting, Finance and Business, 2024)
The food truck business is a new phenomenon among Malaysians today. Food truck business activities among Muslims should be carried out in accordance with rules and procedures that comply with Shariah standards. The concept of Shariah not only governs man in carrying out his life in order to realize the Divine will, but covers all behavior, spiritual, mental as well as physical. Shariah principles also cover the whole way of life which includes beliefs (faith) and practices (deeds), personal, legal and social behavior. The problem that needs to be addressed is the lack of a conceptualized model that is specific to food trucks that complies with the Shariah concept and no halal certification is issued for the food truck business. The objective of the study was to present a Shariah -compliant food truck concept model, provide Shariah guidelines to food truck dealers and facilitate customers to identify Shariah -compliant food trucks. Library research and research methods will be used to gather information related to Shariah -compliant food truck concept models. The results of this study will provide a complete picture related to the concept of Shariah -compliant food truck transactions. The new concept of food truck presented is in line with Islamic requirements and current trends. In fact, it should be highlighted and practiced to increase the dignity of Islamic teachings among the community. It is hoped that the concept presented can be applied in the operation of Shariah -compliant food truck business in Malaysia.